Learning software apps with the English Language Club - S.I.P. 2021 / Noor Azli Affendy Lee, Nur Ilianis Adnan and Muhammad Aiman Abdul Halim - Affendy Lee, Noor Azli; Adnan, Nur Ilianis; Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2022)
The English Language Club of UiTMCPP conducted a Knowledge-Transfer Programme (KTP) called the Software Intellectual Programme (SIP) 2021 which featured student facilitators teaching semester 1 students of UiTMCPP on how to use various software applications that are vital in their university studies and lifelong learning. The SIP 2021 project was proposed as a way to help new diploma and pre-diploma students in understanding and using several useful software applications such as Microsoft Word, Microsoft PowerPoint, and video editing tools that are required for their future assignments in their respective courses.